Argument Structure in Learner Writing: A Corpus-based Analysis Using Argument Mapping - Simon Philip Botley (Kajian Malaysia, 2014)
In this paper, corpus-based linguistics (CBL) is applied to the analysis of argument structure in Malaysian written learner English. Botley and Metom (2011) have demonstrated the value of using a corpus of student essays, a "learner corpus", to explore the interlanguage (Selinker, 1972) of learners in the Malaysian university setting. This paper goes further by focusing on the critical thinking and argumentation abilities of students writing in a foreign language. The data consists of a sample of argumentative essays from the CALES learner corpus (Corpus Archive of Leaner English in Sabah/Sarawak). The essays were all written by Malay L1 students at a major Malaysian public university between 2005 and 2011. Because the essays were argumentative in terms of task type, it is reasonable to expect that the data should yield rich information on the argumentation strategies used by the students in writing their essays. In order to study these argumentation strategies, this paper makes use of a graphical representation scheme for arguments, known as "argument mapping" (Horn, 1999; ter Berg and van Gelder, 2007). Argument maps are diagrams consisting of square boxes linked with arrows, which can be used to represent various aspects of argumentation such as conclusions, premises, claims, contentions, reasons and objections. Using the argument mapping technique, this study seeks empirical data on how Malaysian undergraduates may structure their written arguments. This is currently a bottom-up exploratory study with few pre-set hypotheses. Despite this, it is hoped that the findings will lead to useful insights into how the writers of the essays manage, or do not manage, to construct clear, well-reasoned arguments. The findings should also be very helpful to educators and researchers in areas such as English for Academic Purposes (EAP) and critical thinking.